2018
DOI: 10.1155/2018/2056290
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Usability Issues in Instant Messaging Apps on iOS and Android Platforms

Abstract: With the rise of mobile devices and the high number of instant messaging applications available in the stores, it is necessary to evaluate the usability of such applications to provide a more satisfying user experience. To this end, this paper presents a methodical usability evaluation of instant messaging applications both in iOS and Android platforms. A predefined evaluation was used, which was created to detect the main usability issues of mobile applications, regardless of the device used and the evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 46 publications
1
27
0
1
Order By: Relevance
“…Usability is defined as the effectiveness, efficiency and satisfaction with which the student achieves specific goals in the online learning environment [31]. In this current study, it was found that students in Mauritius could easily use WhatsApp to record lectures and send them to their classmates who could not attend on-campus tutorials.…”
Section: B Greater Usabilitymentioning
confidence: 71%
“…Usability is defined as the effectiveness, efficiency and satisfaction with which the student achieves specific goals in the online learning environment [31]. In this current study, it was found that students in Mauritius could easily use WhatsApp to record lectures and send them to their classmates who could not attend on-campus tutorials.…”
Section: B Greater Usabilitymentioning
confidence: 71%
“…Many Instant messaging applications have been developed which offer more features than just sending of texts, now people can send images, videos, audios, contacts, documents, locations and so on. In as much as these mobile devices and instant messaging applications have made communication so much easier and better, there are other factors that come to play, factors which include the simplicity to learn how to use these devices and applications, the ease at which they can be used, and the satisfaction derived while using them [6]. As earlier mentioned, there are companies that produce different brands of these mobile devices with different Operating systems (OS) running on them and most time, if not all the time, instant messaging applications are designed for the for specific devices or the OSs.…”
Section: Introductionmentioning
confidence: 99%
“…As earlier mentioned, there are companies that produce different brands of these mobile devices with different Operating systems (OS) running on them and most time, if not all the time, instant messaging applications are designed for the for specific devices or the OSs. People like applications and devices that are simple, accessible, comfortable and usable and usually go for the brand and the applications that meet these needs [6]. Today there are two most used brands of mobile devices; iPhones and Samsung S series smartphones and a single most used instant messaging application, WhatsApp Messeng er.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be borne in mind that they are the most used electronic devices [2], with more than 3 billion smartphones [3]. Along with the use of mobile phones, mobile applications (thereafter called, simply, ''apps'') are experiencing an exponential growth in their usage: Between 2009 and 2020, an increase in the number of available mobile apps was reported from 16 thousand apps to 2.9 million apps in Google Play Store and from 25 thousand apps to 1.8 million apps in Apple Apps Store [4][5][6].One type of mobile applications with a growing usage is Mobile Instant Messaging apps (namely, MIM or IM apps), with a high number of active users [7,8], as an evolution of SMS messages [9] and as an improvement of social relationships [10].Nevertheless, when we put together and observe mobile devices, instant messaging apps, and usability, previous studies have found several usability issues in their usage [11][12][13][14][15][16]. Given the fact that creating and attracting users to use a MIM app does not require too much effort, improving usability should be the key to maintain users using the app [17,18].…”
mentioning
confidence: 99%